Zapomniana inwestycja. Niezrealizowana koncepcja budowy Wojewódzkiego Szpitala Specjalistycznego w Zielonej Górze = Forgotten investment. Shelved project ? construction of the Regional Specialist Hospital in Zielona Góra - Skobelski, Robert (1968- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Development of the Regional Hospital in Zielona Góra in the seventies of the last century did not keep up with the increasing number of the town inhabitants. The facility suffered from the lack of premises the most important of which was the lack of specialist wards. Similar difficult conditions were characteristic for the majority of the other hospitals operating at the time in the Province. In view of the problem central authorities decided to construct a new specialist hospital in Zielona Góra. Unfortunately, the project was never implemented due to the escalating political and economic crisis at the turn of the seventies.
Keywords: Zielona Góra; szpital zielonogórski